2013
DOI: 10.2147/jaa.s38652
|View full text |Cite
|
Sign up to set email alerts
|

Utility of adjunctive macrolide therapy in treatment of children with asthma: a systematic review and meta-analysis

Abstract: BackgroundThe purpose of this study was to investigate macrolides as an adjunct to an asthma controller regimen in children with asthma.MethodsProspective clinical trials of macrolide therapy in children with asthma using outcome measures of change in forced expiratory volume in one second (FEV1) and/or oral corticosteroid requirement were searched for in PubMed up to December 2009. The reference lists of studies were also included in the analysis, as well as those listed in published meta-analyses.ResultsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although an official document and a recent pragmatic review do not recommend the routine use of macrolides for children with severe asthma (9, 64), they may be useful for reducing daily oral steroid administration and improving FEV 1 (65), and, for this reason, can be proposed as ex-juvantibus trial in children with neutrophilic asthma (66). In conclusion, further well-designed and large RCTs are warranted before routine use of macrolides is recommended or definitely condemned in pediatric severe asthma.…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
“…Although an official document and a recent pragmatic review do not recommend the routine use of macrolides for children with severe asthma (9, 64), they may be useful for reducing daily oral steroid administration and improving FEV 1 (65), and, for this reason, can be proposed as ex-juvantibus trial in children with neutrophilic asthma (66). In conclusion, further well-designed and large RCTs are warranted before routine use of macrolides is recommended or definitely condemned in pediatric severe asthma.…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
“…Macrolides have been also proposed in combination to the treatment regimen of asthmatic children, with the aim of decreasing the need of the patient's daily dosage of corticosteroids, due to its antinflammatory and antimicrobial activity ( 49 ). A recent study including 40 school-aged asthmatic children showed that a 3-week course of clarythromicyn given as add-on therapy to regular treatment, was associated with an increased control of symptoms and a decrease in the duration of the asthma exacerbations ( 50 ).…”
Section: Other Pharmacological Optionsmentioning
confidence: 99%